2010
DOI: 10.1128/mcb.00645-09
|View full text |Cite
|
Sign up to set email alerts
|

Friend of Prmt1, a Novel Chromatin Target of Protein Arginine Methyltransferases

Abstract: We describe the isolation and characterization of Friend of Prmt1 (Fop), a novel chromatin target of protein arginine methyltransferases. Human Fop is encoded by C1orf77, a gene of previously unknown function. We show that Fop is tightly associated with chromatin, and that it is modified by both asymmetric and symmetric arginine methylation in vivo. Furthermore, Fop plays an important role in the ligand-dependent activation of estrogen receptor target genes, including TFF1 (pS2). Fop depletion results in an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 53 publications
6
65
0
Order By: Relevance
“…Like the nuclear SMN, the expressed HB-FOP was extracted more efficiently under the high salt condition than the low salt condition ( Figure 3B). This is consistent with the report of van Dijk et al [26] which demonstrated that FOP was associated with chromatin, localized mainly in facultative heterochromatin region, and thus was extracted mostly under high salt conditions. Biotin affinity Figure 3C and Table 1 and Supplementary Table 3).…”
Section: The Fop-associating Smn Complexes Do Not Contain U1 and U2 Ssupporting
confidence: 93%
See 4 more Smart Citations
“…Like the nuclear SMN, the expressed HB-FOP was extracted more efficiently under the high salt condition than the low salt condition ( Figure 3B). This is consistent with the report of van Dijk et al [26] which demonstrated that FOP was associated with chromatin, localized mainly in facultative heterochromatin region, and thus was extracted mostly under high salt conditions. Biotin affinity Figure 3C and Table 1 and Supplementary Table 3).…”
Section: The Fop-associating Smn Complexes Do Not Contain U1 and U2 Ssupporting
confidence: 93%
“…FOP is also required for the association of SMN complexes with a number of hnRNPs and RNA binding proteins (Step 3 in Figure 5). Based on these data and the previous reports [26], we propose that FOP-SMN complex has a role in retaining spliced and/or unspliced mRNAs in near the transcription sites on chromosome. This does not conflict to the previous notion that FOP has a critical role in specific mRNA transcriptional regulation and mRNA export [27,28].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations